2004
DOI: 10.1037/0022-006x.72.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Insomnia: Comparison of Individual Therapy, Group Therapy, and Telephone Consultations.

Abstract: Forty-five adults with primary insomnia received cognitive-behavioral therapy (CBT) implemented in a group therapy format, in individual face-to-face therapy or through brief individual telephone consultations. The results indicate that CBT was effective in improving sleep parameters with all 3 methods of treatment implementation, and there was no significant difference across methods of implementation. All 3 treatment modalities produced improvements in sleep that were maintained for 6 months after treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
134
3
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(153 citation statements)
references
References 24 publications
2
134
3
12
Order By: Relevance
“…However, we could not compare this effect size with the results of a previous Internet-based study because the previous study did not report an effect size 9) . Our observed effect size, however, seems comparable with those reported in previous studies of non-Internet-based self-help treatment based on CBT or BT 10,12,13) . The marginally significant reduction of sleep-onset latency is consistent with previous nonInternet-based studies that have reported that stimulus control/sleep restriction was associated with improvement in sleep latency 31) .…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…However, we could not compare this effect size with the results of a previous Internet-based study because the previous study did not report an effect size 9) . Our observed effect size, however, seems comparable with those reported in previous studies of non-Internet-based self-help treatment based on CBT or BT 10,12,13) . The marginally significant reduction of sleep-onset latency is consistent with previous nonInternet-based studies that have reported that stimulus control/sleep restriction was associated with improvement in sleep latency 31) .…”
Section: Discussioncontrasting
confidence: 53%
“…To our knowledge, this is the first randomized controlled trial to evaluate a self-help intervention program for better quality of sleep in a working population. Since most of the self-help programs for insomnia in previous studies required more than one month of participation 9,10,[12][13][14][15][16] , these seemed too demanding, particularly when applied to people with a job.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De oefeningen en de lichaamsbeweging kunnen cliënten in de dagplanning opnemen. -Slaaphygiëne (Bastien, Morin, Quellet, Blais, & Bouchard, 2004;Waterman & Hofman, 1996). De cliënten krijgen uitleg, onder andere over de negatieve invloed van middagdutjes, cafeïne, alcohol en slaapmedicatie op de kwaliteit van slapen.…”
Section: Fase 2 Bewustwording: Stemmingsmeterunclassified
“…There is a growing body of evidence for these less intensive interventions: CBT-I in selfhelp formats, such as bibliotherapy and audiotape, may be comparable to face-to-face treatments for improving self-reported insomnia severity, particularly when accompanied by telephone consultations (Ho et al, 2015;van Straten & Cuijpers, 2009). Group CBT-I is shown to be effective for improving diary-derived outcomes such as sleep efficiency (SE), sleep onset latency (SOL), and wake time after sleep onset (WASO; Bastien, Morin, Ouellet, Blais, & Bouchard, 2004;McCurry, et al, 2014), although the evidence base is smaller than for individual CBT. Brief, nurse-led CBT-I interventions delivered in primary care have been associated with significant improvements in sleep quality and clinical measures of depression and anxiety (Espie et al, 2007).The effects of these briefer therapies may also be maintained in the long term.…”
mentioning
confidence: 99%